Water relations, carbon fixation and growth rates of two leaf succulent species under different water regimes - Beukman, Ruth Pam (Department of Biological Sciences, 2023)
The leaf succulent species R.carolii and R.multiflora are common in the winter rainfall Karoo. Despite their similar growth form, their distribution in Worcester Veld Reserve appeared to differ. R.multiflora occupied a more exposed, arid North - facing slope, while R.carolii dominated a protected South facing slope. Possible reasons for this distribution were investigated. Plants of the two species were established in a growth chamber and subjected to different water regimes. The diurnal patterns of water loss and ca1rbon gain were investigated under optimal and drought conditions after 30, 50 and 60 days of treatment. Gas exchange data of both species showed that C3 photosynthesis was adopted when ·the plants - were irrigated regularly, but also tended to accumulate malate, which indicated the activity of RuBPc and PEPc. R.carolii had higher photosynthetic and growth rates than R.multiflora under optimal conditions. This explained the dominance of R.carolii on the South facing, protected slope. Under moderate water stress, the species behaved similarly. There was a tendency towards CAM activity, though results were inconclusive. During periods of extreme water shortage. R.carolii exhibited limited stomatal response and thus appeared to be dying, while R.multiflora adopted day time stomatal opening a and CO2 uptake. This strategy and in general the high tolerance to water stress shown by R.multiflora allowed it to outcompete R.carolii on the arid, exposed, North facing slope.